Electrochemistry combined-surface plasmon resonance biosensors: A review - Ribeiro, José (2022)
Over the years, most of the literature reported applications of electrochemical and surface plasmon resonance (SPR) immunoassays for biosensing but, so far, the combination of the two methods in the same sensing spot for analytical purposes is much less explored and discussed. The aim of this Review is to highlight the great potential of electrochemistry combined-SPR (eSPR) as analytical tool for screening chemically and biologically relevant (bio)molecules by combining the unique features of SPR integrated with electrochemical readout. In the first part of the Review, we describe the urgent need of innovative methods for screening clinical biological markers (General Introduction), briefly discuss general concepts of SPR and electrochemical sensing (Concepts behind eSPR biosensors) and highlight the hyphenation of two methods to developed combined biosensing systems (Set-up configuration and eSPR principles). Firstly, we briefly give an overview of the setup for implementation of eSPR technique and discuss some relevant experimental conditions to perform the combined optical and electrochemical measurements. Then, the principles and fundamentals of eSPR biosensors are presented and described. We also present representative examples of eSPR biosensors in the literature (Applications of eSPR biosensors). In the second part, we review studies on how combined electrical and plasmonic detection contributed to the biosensing field, in particular, for the successful screening of clinically relevant biomolecules, namely proteins (Detection of proteins), nucleic acids (Detection of nucleic acids), small size chemical species (Detection of small molecules) and cells (Living-cell Analysis). Finally, we discuss the current limitations of eSPR biosensors performance and suggest possible ways to overcome these limitations (Limitations and optimization) and then we explore aspects about the development of the method and its applications and discuss areas of likely future growth (Conclusions and perspectives).